2008
DOI: 10.1002/chem.200800070
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Near‐IR Spectral Properties of Individually Dissolved Single‐Walled Carbon Nanotubes in Aqueous Solutions of dsDNA

Abstract: Two different single-walled carbon nanotubes (SWNTs), the so-called HiPco and CoMoCAT, have been individually dissolved in aqueous solutions of double-stranded DNA (dsDNA). Atomic force microscopy (AFM) revealed the fine structures of the dsDNA-wrapped SWNTs. The near-IR absorption and photoluminescence (PL) spectra of aqueous solutions of dsDNA-wrapped SWNTs were recorded and, in pure water, we observed only a single two-dimensional PL spot from (6,5) SWNTs for both HiPco and CoMoCAT. In sharp contrast, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Raising the pH of the solution is able to deprotonate the surface oxides, thus recovering the nanotubes' optical properties. This behaviour is known to occur in SDS-based suspensions [28], as well as for DNA [29,30] and poly(maleic acid/octyl vinyl ether) [16], however it does not appear to occur in dispersion of CNTs with many other surfactants [31], at least not to the same extent. This is most likely due to the density of the adsorbed surfactant layer and the corresponding ability of that layer to exclude oxygen from the nanotube surface [29].…”
Section: Resultsmentioning
confidence: 81%
“…Raising the pH of the solution is able to deprotonate the surface oxides, thus recovering the nanotubes' optical properties. This behaviour is known to occur in SDS-based suspensions [28], as well as for DNA [29,30] and poly(maleic acid/octyl vinyl ether) [16], however it does not appear to occur in dispersion of CNTs with many other surfactants [31], at least not to the same extent. This is most likely due to the density of the adsorbed surfactant layer and the corresponding ability of that layer to exclude oxygen from the nanotube surface [29].…”
Section: Resultsmentioning
confidence: 81%
“…[4][5][6][7][8] However, a major barrier for CNT utilizations especially for SWCNTs is their poor solubility and dispersability both in aqueous and organic media. [9,10] They usually tend to form crystalline ropes due to strong inter-tube van der Waals attraction, leading to difficulties in their manipulation and incorporation into different matrixes. A lot of work has been devoted to improve the solubility of CNTs through covalent or non covalent modification.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been devoted to improve the solubility of CNTs through covalent or non covalent modification. [10][11][12][13][14][15][16][17][18] CDs are macrocyclic oligosugars most commonly composed of 6, 7, or 8 glucosidic units named a-, b-, and c-CD, accordingly. [19] They have a hydrophobic inner cavity and a hydrophilic outside surface.…”
Section: Introductionmentioning
confidence: 99%
“…The carbonyl signature of the guanine carbonyl groups in the quadruplex motif was observed at 1695 cm À 1 . 893 IR has also been used to study properties of single-walled carbon nanotubes dissolved in a DNA solution, 646 and to study hydrogen bonding of a guanine in a RNA hairpin, the C6 carbonyl signal occurring at 1669 cm À 1 . 894 …”
Section: Other Structural Methodsmentioning
confidence: 99%
“…The structures of these complexes were found to be different depending upon the pH of the solution, and actual structures depend on the number of holes generated in the SWNTs. 646 SWNTs have been used to mimic intracellular molecular crowding conditions, where it was shown that SWNTs induce i-motif formation and consequent dehydration of the DNA, thus SNWTs may be able to moderate telomeric DNA in vivo. 647 DNA-functionalised SWNTs can accelerate the polymerisation of polyaniline nanocomposites by up to 4500-fold, as well as forming more uniform length polymers.…”
Section: Nanostructures and Nanodevicesmentioning
confidence: 99%